The Strange Case: The Unsymmetric Cisplatin-Based Pt(IV) Prodrug [Pt(CH3COO)Cl2(NH3)2(OH)] Exhibits Higher Cytotoxic Activity with respect to Its Symmetric Congeners due to Carrier-Mediated Cellular Uptake. (30th December 2022) - Gabano, Elisabetta; Zanellato, Ilaria; Pinton, Giulia; Moro, Laura; Ravera, Mauro; Osella, Domenico
Abstract : The biological behavior of the axially unsymmetric antitumor prodrug ( OC -6-44)-acetatodiamminedichloridohydroxidoplatinum(IV), 2, was deeply investigated and compared with that of analogous symmetric Pt(IV) complexes, namely, dihydroxido 1 and diacetato 3, which have a similar structure. The complexes were tested on a panel of human tumor cell lines. Complex 2 showed an anomalous higher cytotoxicity (similar to that of cisplatin) with respect to their analogues 1 and 3 . Their reduction potentials, reduction kinetics, lipophilicity, and membrane affinity are compared. Cellular uptake and DNA platination of Pt(IV) complexes were deeply investigated in the sensitive A2780 human ovarian cancer cell line and in the corresponding resistant A2780cisR subline. The unexpected activity of 2 appears to be related to its peculiar cellular accumulation and not to a different rate of reduction or a different efficacy in DNA platination and/or efficiency in apoptosis induction. Although the exact mechanism of cell uptake is not fully deciphered, a series of naïve experiments indicates an energy-dependent, carrier-mediated transport: the organic cation transporters (OCTs) are the likely proteins involved.